The Effect of Needle Sizes for Sample Adequacy in Thyroid Nodule Fine-Needle Biopsies - Muhammet Arslan; Nagihan Yalçın; Halil Aslan; Pınar Çakmak; Mehmet Alpua; Esra Harktı; Hatice Göktaş (Journal of Contemporary Medicine, 2021)
Aim: The aim of this study was to compare the diagnostic adequacy of thyroid samples obtained with 22-Gauge and 27-Gauge needles. Materials and Methods: From January 2019 to December 2019, 860 patients with thyroid nodules who underwent ultrasound-guided fine-needle biopsies were included in this retrospective study. The results of the samples taken were classified cytologically according to the Bethesda 2017classification. Sample adequacy rates were calculated for each group and compared using chi-square tests. Results: Our cytological results were reported as 157 (18,3%) inadequate materials (Bethesda1). There were no statistically significant differences among the adequacy rates achieved with 22- and 27-gauge needles (80.4% and 83.2%, respectively; P gt;0.05). There was no significant or permanent complication. Conclusion: There was no difference between 22 and 27-Gauge needle sizes in diagnostic adequate sample. Prospective randomized controlled studies are needed to examine the relationships between nodule, needle, and patient dependent variables.